Utilizando redes sociais para a potencialização da aprendizagem em Bioquímica no ensino médio: Uma sequência didática sobre carboidratos. - Augusto Bernardo de Araújo (2023)
The process of teaching and learning Biochemistry content for high school students has been a challenge for Biology students and teachers, since this content, according to the approach adopted in the classroom, can be quite abstract for students at this school stage. At least in part, the difficulties encountered by students in relation to Biochemistry may be related to the lack of connection and contextualization of the discipline's content with everyday events, as well as difficulties associated with other contents, such as physics and organic chemistry. Access to digital technologies, on the other hand, is part of the daily life of students who mostly have smartphones available that can be used to provide the presentation of biochemistry content in an innovative and more interesting way. Thus, in this work we proposed to evaluate the effect of using digital applications and social networks, through smartphones, in the teaching of Biochemistry, to intermediate the teaching-learning process of high school students. Thus, the objective of this work was to evaluate whether active/investigative methodologies associated with the use of social networks favor student learning in a public school in a rural area in the state of Minas Gerais. The theme chosen was the study of the structure and functions of carbohydrates and had as its motivating question the resistance of some organisms, such as the resurrection rose, to desiccation. With the application of the proposed didactic sequence and through a survey questionnaire pre and post activities, it was possible to demonstrate that learning was more effective, probably from the moment that students were given greater meaning in the educational process. With the methodology used, it was possible to verify that the students were actively involved in the construction of knowledge, resulting in significant learning. Furthermore, it was demonstrated that social networks, more specifically Facebook, can and should be used as complementary tools for building and sharing knowledge.